Bilateral ulnar longitudinal deficiency with oligodactyly in newborn - Sofia Cruzes Moysés Simão; Júlia Avelans Pires da Silva; Ariel Ortega Miranda; Rayza de Sousa Costa; Carolina Schlindwein Mariano Ferreira; Regina Yumi Saito (Revista Paulista de Pediatria)
ABSTRACT Objective: The objective of this study was to report a case of bilateral ulnar longitudinal deficiency with oligodactyly in a male newborn. Case description: A full-term male newborn, born following an uncomplicated gestation with no abnormalities detected on prenatal ultrasounds, presented upper limb malformations described as shortening of the left forearm and absence of three digits bilaterally upon neonatal physical examination. Diagnostic investigations including X-rays, abdominal ultrasound, head ultrasound, echocardiogram, and karyotype analysis were conducted, facilitating detailed identification of the malformations and exclusion of other anomalies, thereby suggesting the diagnosis of congenital longitudinal deficiency of the ulna. Discharge planning encompassed supportive care and rehabilitation as per the patient’s needs. Comments: Ulnar longitudinal deficiency is a rare congenital upper limb malformation, whose estimated incidence is 1:100,000 newborns. It is believed to be related to the Sonic Hedgehog gene, and the upper limb anomalies vary according to the ulnar involvement. The early diagnosis is not routine, being more common at the first physical examination with the aid of imaging tests.